A Rare Case of Functioning Adrenocortical Oncocytoma Presenting as Cushing Syndrome - Nicola Tartaglia; Pasquale Cianci; Amedeo Altamura; Vincenzo Lizzi; Fernanda Vovola; Alberto Fersini; Antonio Ambrosi; Vincenzo Neri (Case Reports in Surgery)
Functioning adrenocortical oncocytoma is very rare neoplasm. It is usually nonfunctional and benign and incidentally detected. Generally, these tumors originate in the kidneys, thyroid, parathyroid, and salivary or pituitary glands; they have also been reported in other sites including choroid plexus, respiratory tract, and larynx. Histologically, they are characterized by cells with eosinophilic granular cytoplasm and numerous packed mitochondria. We reported a case of a 44-year-old female who presented with Cushing syndrome for hypersecretion of cortisol due to adrenocortical oncocytoma. Magnetic resonance of abdomen revealed a right adrenal mass. Laparoscopic adrenalectomy was performed and the tumor was pathologically confirmed as benign adrenocortical oncocytoma. After surgical treatment, Cushing’s syndrome resolved.